The Politics of Independent Curriculum Policy and the Challenge of Equal Education in Indonesia - Fikratul Munawarah; Avrilia Puja; Nur Amin Nurdin; Abdul Haq'e; Nabila Zalzabila T (Early Publishing, 2026)
This study aims to analyze the political dynamics of the independent curriculum policy and examine the challenges of education equity in Indonesia. The research uses a qualitative approach with the library research method. Data was obtained from various secondary sources in the form of scientific journal articles, books, government policy documents, and regulations related to the independent curriculum, education politics, and educational equity. The data collection technique is carried out through documentation studies, while data analysis uses content analysis with a qualitative descriptive approach through the stages of data reduction, categorization, interpretation, and literature synthesis. The results of the study show that the independent curriculum is a form of education policy reform that is oriented towards learning flexibility, strengthening competencies, and developing students' character. Its implementation provides a wider space for schools and teachers to develop learning according to the needs of students and the local context. However, the implementation of the policy still faces various challenges, including inequality in the quality of human resources, limited facilities and infrastructure, gaps in access to technology, and differences in local government capacity which have an impact on the uneven quality of education in Indonesia. Therefore, the success of the implementation of the independent curriculum is not only determined by the quality of the policies formulated, but also requires sustainable political commitment, equitable distribution of educational resources, strengthening teacher competence, and synergy between stakeholders to realize inclusive, quality, and equitable education.